Sacred biography in the Buddhist traditions of South and Southeast Asia - Schober, Juliane (Honolulu, Hawaii : University of Hawai'i Press, 1997)
This collection of previously unpublished essays presents a broad range of explorations into the biographical genre of the Buddhist traditions of South and Southeast Asia. Each contribution examines sacred biography in one or more representational modalities in the texts, art history, literature, myths, rituals and cultures of the Buddhist tradition. Scholars in the history of religions, anthropology, literature and art history present a broad range of explorations into sacred biography as an interpretive genre. The essays investigate both universal and local articulations of Buddhist sacred biography, illustrating the construction of interpretive frames of reference that map salient themes onto diverse contexts. The combination of thematic depth and theoretical sophistication in Sacred Biography makes this volume innovative reading for all scholars with comparative interests.
Frontmatter -- Contents -- Preface -- Trajectories in Buddhist Sacred Biography / Schober, Juliane -- Buddha Biography in Textual and Visual Narratives -- Rebirth Traditions and the Lineages of Gotama: A Study in Theravāda Buddhology / Reynolds, Frank E. -- The Biographical Imperative in Theravāda Buddhism / Woodward, Mark R. -- Narrative as Icon: The Jātaka Stories in Ancient Indian and Southeast Asian Architecture / Brown, Robert L. -- Extensions of the Buddha Biography in Texts -- A Family Quest: The Buddha, Yaśodharā, and Rāhula in the Mūlasarvāstivāda Vinaya / Strong, John S. -- Nāgārjuna's Longevity / Ray, Reginald A. -- Stūpa, Story, and Empire: Constructions of the Buddha Biography in Early Post-Aśokan India / Walters, Jonathan S. -- The Jātakas and Biographies of Kings -- Painting the "Great Life" / McGill, Forrest -- From Prose to Poetry: The Literary Development of Samuttakote / Hudak, Thomas John -- "Rationality" in the Biography of a Buddhist King: Mongkut, King of Siam (r.1851-1868) / Johnson, Paul Christopher -- The Biographical Genre in Local Buddhist Cults and Practice -- In the Presence of the Buddha: Ritual Veneration of the Burmese Mahāmuni Image / Schober, Juliane -- The Textualization of a Monastic Tradition: Forest Monks, Lineage, and the Biographical Process in Thailand / Taylor, James L. -- The Biography of Modern Burmese Buddhist Meditation Master U Ba Khin: Life before the Cradle and past the Grave / Houtman, Gustaaf -- Index -- About the Contributors.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Gautama Buddha; Gautama Buddha; Buddhist saints -- Biography -- History and criticism; Buddhist hagiography -- History and criticism; Saints bouddhistes -- Biographies -- Histoire et critique; Hagiographie bouddhique -- Histoire et critique; RELIGION -- Buddhism -- General; Buddhist hagiography; Buddhist saints -- Biography; Electronic books; Criticism, interpretation, etc